2003
DOI: 10.1124/mol.63.1.192
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Telomerase Increases Resistance of Melanoma Cells to Temozolomide, but Not to Temozolomide Combined with Poly (ADP-Ribose) Polymerase Inhibitor

Abstract: In the present study, we have investigated the influence of telomerase inhibition in chemosensitivity of melanoma cells to temozolomide (TMZ), a methylating agent with promising antitumor activity against metastatic melanoma. In fact, telomerase, a ribonucleoprotein enzyme expressed in the majority of tumors, is presently considered an attractive target for anticancer therapy, with the double aim of reducing tumor growth and increasing chemosensitivity of cancer cells. Susceptibility to TMZ and to other antitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Malignant glioma cells were sensitised to cisplatin by inhibition of telomerase (Kondo et al, 1998b). Furthermore, inhibition of telomerase resulted in increased sensitivity to cisplatin, but increased resistance to TMZ in melanoma cells (Tentori et al, 2003). Therefore, the relationship between levels of telomerase activity in tumour cells prior to anticancer therapies and their sensitivity to therapeutic agents may depend on the type of cell or treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignant glioma cells were sensitised to cisplatin by inhibition of telomerase (Kondo et al, 1998b). Furthermore, inhibition of telomerase resulted in increased sensitivity to cisplatin, but increased resistance to TMZ in melanoma cells (Tentori et al, 2003). Therefore, the relationship between levels of telomerase activity in tumour cells prior to anticancer therapies and their sensitivity to therapeutic agents may depend on the type of cell or treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the present study, TMZ-sensitive and -resistant malignant glioma cells express a similar high level of telomerase. As suggested by Tentori et al (2003), TMZ sensitivity seems to be dependent mainly on Aliquots of 1 mg protein extract were used for assay. The amplification products were applied to a 10% polyacrylamide gel and stained using SYBR Green.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that inhibition of telomerase using the DN-hTERT construct not only limits the growth of tumor cells, but also sensitizes them to anti-neoplastic drugs (Misawa et al 2002, Tentori et al 2003. In this context, we recently used the DN-hTERT construct in order to demonstrate the involvement of telomerase in the chemosensitivity of melanoma cells.…”
Section: Dominant-negative Htertmentioning
confidence: 99%
“…Here, addition of 3-aminobenzamide restored the cytotoxic effects of TZM. 25 In summary, the combined treatment of tumour cells in vitro and, more important, in vivo with chemotherapeutic compounds such as alkylating agents or topoisomerase-1 inhibitors and PARP inhibitors yielded beneficial effects such as increasing the number of DNA strand breaks, growth inhibition and cell killing and thus enhancement of the survival of tumour-bearing animals. But it also has to be noted that the components of any such combinatorial treatment have to be selected carefully to avoid deleterious effects.…”
Section: Cancer Therapymentioning
confidence: 99%